Improving the hydrogen peroxide bleaching efficiency of aspen chemithermomechanical pulp by using chitosan. (5th November 2015) - Li, Zongquan; Dou, Hongyan; Fu, Yingjuan; Qin, Menghua
Highlights: Chitosans improved the brightness of the hydrogen peroxide bleached CTMP. Chitosans inhibited the peroxide decomposition catalyzed by copper and manganese. Chitosans slightly inhibited the formation of the hydroxyl radical. Abstract: The presence of transition metals during the hydrogen peroxide bleaching of pulp results in the decomposition of hydrogen peroxide, which decreases the bleaching efficiency. In this study, chitosans were used as peroxide stabilizer in the alkaline hydrogen peroxide bleaching of aspen chemithermomechanical pulp (CTMP). The results showed that the brightness of the bleached CTMP increased 1.5% ISO by addition of 0.1% chitosan with 95% degree of deacetylation during peroxide bleaching. Transition metals in the form of ions or metal colloid particles, such as iron, copper and manganese, could be adsorbed by chitosans. Chitosans could inhibit the decomposition of hydrogen peroxide catalyzed by different transition metals under alkaline conditions. The ability of chitosans to inhibit peroxide decomposition depended on the type of transition metals, chitosan concentration and degree of deacetylation applied. The addition of chitosan slightly reduced the concentration of the hydroxyl radical formed during the hydrogen peroxide bleaching of aspen CTMP.